EVALUATION OF THE TEACHER PROFESSIONAL EDUCATION PROGRAM (PPG): ENGLISH STUDENTS’ PERSPECTIVE - Afrianto Daud; Novitri Novitri; Mirza Hardian (AL-ISHLAH: Jurnal Pendidikan, 2020)
This study aims to document the assessment of alumni of teachers professional education program (PPG) in Riau University on the effectiveness of the PPG program in preparing prospective professional English teachers. All alumni of the 2018 subsidized PPG program at the University were selected as the sample of this study (15 people). Data was collected through the distribution of a Google form-based survey which was adopted from the PPG program evaluation questionnaire from the Ministry of Education, Higher Education. This study found that from the curriculum aspect, 84.6% of alumni said that the PPG curriculum content was in accordance with the needs of pre-service English teachers. However, 76.9% of participants stated that most of the material had been studied when they were in the undergraduate program. In terms of learning facilities, only 23.1% answered that they were satisfied with PPG facilities. 46.2% of them stated that the lecture room was not feasible. From the aspect of organizing services to students, only 42.6% said they were satisfied. The rest answered simply enough. From the aspect of the impact of the program, 69.2% of participants admitted that PPG had a significant impact on the development of their teaching profession. The greatest impact is on the aspect of both professional and pedagogical competencies. Thus, even though PPG is generally considered to be running quite well and has a positive impact, there are several aspects that need to be the attention of PPG organizers for the improvement of PPG in the future.